2019
DOI: 10.1016/j.scitotenv.2018.11.265
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated vs new advanced treatment methods for the removal of contaminants of emerging concern from urban wastewater

Abstract: Consolidated vs new advanced treatment methods for the removal of contaminants of emerging concern from urban wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
284
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(300 citation statements)
references
References 220 publications
(292 reference statements)
5
284
0
11
Order By: Relevance
“…This may conduct to poisonous and opposite impacts on aquatic organisms and thus on human beings. Regrettably, WWTPs are not planned to eliminate CECs; moreover, secondary (such as traditional activated sludge process, CAS) and tertiary (like filtration and disinfection [ [65] reviewed the state of the art and the best available technologies for the advanced treatment of municipal wastewater. Especially, they deeply discussed the data [66] obtainable on consolidated (ozonation, AC and membranes [67]) and novel advanced treatment methods (fundamentally AOPs) to assess ( Figure 1 eliminating CECs from wastewater, 2) benefits and inconvenients, 3) likely barriers to using AOPs, 4) practical restrictions and mid to long-term estimations for employing heterogeneous processes, and 5) a technical and economic comparison between the numerous processes/technologies.…”
Section: Treating Municipal Wastewater: From Consolidated To New Advamentioning
confidence: 99%
See 1 more Smart Citation
“…This may conduct to poisonous and opposite impacts on aquatic organisms and thus on human beings. Regrettably, WWTPs are not planned to eliminate CECs; moreover, secondary (such as traditional activated sludge process, CAS) and tertiary (like filtration and disinfection [ [65] reviewed the state of the art and the best available technologies for the advanced treatment of municipal wastewater. Especially, they deeply discussed the data [66] obtainable on consolidated (ozonation, AC and membranes [67]) and novel advanced treatment methods (fundamentally AOPs) to assess ( Figure 1 eliminating CECs from wastewater, 2) benefits and inconvenients, 3) likely barriers to using AOPs, 4) practical restrictions and mid to long-term estimations for employing heterogeneous processes, and 5) a technical and economic comparison between the numerous processes/technologies.…”
Section: Treating Municipal Wastewater: From Consolidated To New Advamentioning
confidence: 99%
“…Especially, they deeply discussed the data [66] obtainable on consolidated (ozonation, AC and membranes [67]) and novel advanced treatment methods (fundamentally AOPs) to assess ( Figure 1 eliminating CECs from wastewater, 2) benefits and inconvenients, 3) likely barriers to using AOPs, 4) practical restrictions and mid to long-term estimations for employing heterogeneous processes, and 5) a technical and economic comparison between the numerous processes/technologies. Rizzo et al [65] concluded that:…”
Section: Treating Municipal Wastewater: From Consolidated To New Advamentioning
confidence: 99%
“…In addition, the accumulated UV-A energy per unit of treated water volume dose (QUV), in terms of kJ/L, is a key parameter to monitor the microorganism inactivation under UV radiation in the function of treatment time when the system is photo-limited [49]. Nonetheless, the interest in ozone treatments is increasing since this chemical has the power to inactivate microbial cells and to decrease the load of organic chemicals [46,50].…”
Section: Introductionmentioning
confidence: 99%
“…Effluents of fish farms are another direct source of ECs for surface water (Kim et al, 2017). However, conventional wastewater treatment processes fail in removing ECs (Huber et al, 2005;Rigobello et al, 2013;Zhang et al, 2017;Delgado-Moreno et al, 2019;Rizzo et al, 2019). Taking into account that drinking water (DW) is often produced from surface water and groundwater, the efficacy of ECs removal through drinking water treatment plants (DWTPs) is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%